2009
DOI: 10.1017/s0022215109005246
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical osteophytes resulting in severe dysphagia and aspiration: two case reports and literature review

Abstract: In patients with anterior cervical osteophytes, surgical treatment is indicated only for selected cases with large, bony osteophytes and severe symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 25 publications
0
34
0
2
Order By: Relevance
“…Eight cases were reported from eastern Asia, four each from Japan and Korea [24][25][26][27][28][29]. Two case reports were from Netherlands [30]. Singapore, India, France, Austria, Taiwan, Australia, Iran, Saudi Arabia, Puerto Rico and Greece added single case each to the list [31][32][33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…Eight cases were reported from eastern Asia, four each from Japan and Korea [24][25][26][27][28][29]. Two case reports were from Netherlands [30]. Singapore, India, France, Austria, Taiwan, Australia, Iran, Saudi Arabia, Puerto Rico and Greece added single case each to the list [31][32][33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there are other mechanisms that cause dysphagia. Several possible explanations other than direct obstruction have been put forward: Several studies suggested neuropathy due to recurrent laryngeal nerve injury as a result of ongoing inflammation and fibrosis of the esophagus secondary to 8 osteophyte irritation as a cause [9][10][11][12][13][14] . One case report indicated a palsy of the left vocal cord due to pressure on the recurrent laryngeal nerve 15) .…”
Section: Discussionmentioning
confidence: 99%
“…There is a controversy in the literature concerning the appropriate treatment of 9 dysphagia due to Forestier's disease 10) . The recommended first-line approach has been observation or diet modification and a regimen of anti-inflammatory medications 17) .…”
Section: Discussionmentioning
confidence: 99%
“…The thoracic region is almost always involed (96%). The lumbar (90%) and cervical regions (78%) are affected to a lesser extent [4, 6, 7]. At times, soft tissue thickening and calcification can olso occur at peripheral joints, particularly the femur, patella or the metatarsal joint [4, 8, 9].…”
Section: Discussionmentioning
confidence: 99%